Carbon sequestration law by phytoliths in the bamboo forests: Insights for the management of phytolith carbon sink - Li Liu; Linjiao Wang; Lukang Song; Maoyin Sheng (Global Ecology and Conservation)
Phytolith-occluded organic carbon (PhytOC) plays a crucial role as a stable and enduring carbon sink in the intricate web of terrestrial ecosystems. Bamboo forests exhibit the most prominent ability of phytolith carbon sequestration among terrestrial vegetation. This study systematically investigated the complex dynamics of phytolith carbon sequestration and accumulation in different organs (leaves, branches, culms, and roots) of P. edulis and B. emeiensis forests across three growth stages (young, middle-aged, and mature) in shale and limestone regions of southwest China. The results unveiled the spectrum of PhytOC content, storage, and sequestration rate within the P. edulis forests, ranging from 0.24 to 10.51 g·kg−1, 0.62–35.72 kg·hm−2, and 0.75–61.06 kg·CO2·hm−2·a−1, respectively. On the other hand, the B. emeiensis forests exhibited a wider range, with PhytOC content varying from 0.33 to 20.59 g·kg−1, storage from 0.25 to 102.81 kg·hm−2, and sequestration rate from 0.90 to 75.39 kg·CO2·hm−2·a−1. The differences in phytolith carbon sequestration were significant or extremely remarkable across forest species, ages, organs, and bedrock types. Roots play a major role in the phytolith carbon sequestration of bamboo forests. The root PhytOC sequestration rate of P. edulis and B. emeiensis is 30.67 and 12.69 kg·CO2·hm−2·a−1, respectively. Forest age and bedrock both have a significant impact on the phytolith carbon sequestration of bamboo forests. Both soil physicochemical properties and forest community structures are closely related to phytolith carbon sequestration and accumulation in the bamboo forests, which are great of significance in the artificial intervention for increasing the phytolith carbon sink.